Modelagem matemática nas licenciaturas em matemática das universidades estaduais do Paraná - Oliveira, Wellington Piveta (2016)
Discussions about research and practices with Mathematical Modeling in the perspective of Mathematics Education have been recurrent in the Mathematics teacher education. Based on this statement and understanding that the discussions on this topic - teacher education - is relatively new in the community, this study shows contributions to stimulate discussion and deepening of Modeling in this context. Also provides a comprehensive insight into the teacher education process and reveals the manifestation of Modeling in degree courses in Mathematics of the state universities of Paraná. The research gave birth to the question: "What is revealed about the presence of Mathematical Modeling in Mathematics Education in Mathematics undergraduate courses in the state universities of Paraná?" under the principles of qualitative research, assuming the phenomenological-hermeneutic approach. Thus, so that we could proceed with the research, we investigated the disciplines menus of Mathematics degree courses of the state universities of Paraná, which were made available in the electronic site of each institution and we map those courses that offer the Mathematical Modeling discipline in 2014, as mandatory. After this mapping, we contact the course coordinators to confirm the existence, the occurrence of discipline and doing the invitation to participate in the survey. That done, we seek to establish the means by which the Modeling could manifest and how it could tell us about their presence. Thus, delimited as a tool to collect testimonies of teachers who worked with discipline in 2014, because we have not identified any research in the literature that investigate this aspect. And also, the teaching plans of the subjects constituted our data list. Approved the design of this research by the Ethics Committee of the University, we took about four months to accomplish the collection. Collected the testimonies, we began to transcribe them and following use an Atlas t.i. Therefore, when we enter into the software the statements of eight participating teachers as well as the eight teaching plans of disciplines, we seek for meaning units that could reveal clues about the presence of Modeling in the courses. Highlighted these units, even in the software, we establish convergence between them, which led to the six units of meaning. Then, each of the them has been described and performed collectively in a metatext. The insights enabled by this interpretation revealed that the phenomenon focused, Mathematical Modeling is manifesting under two models. In the first, a teacher education with Mathematical Modeling in Mathematics Education and in the second, the development of Modeling as the method, assigned to the degree model. In addition, other aspects have emerged contributed to the debate on the presence of Modeling as a trend in the Mathematics degree courses and not being episodic as it has been presented. Indeed, it requires a restructuring practices and calls for a break with the disciplinary boundaries of these courses, so that the activities and theoretical reflections can permeate these teacher education contexts and transitively enable an effectively Modeling implementation